The Emotional Life of Contemporary Public Memorials Towards a Theory of Temporary Memorials - Doss, Erika (Meertens Ethnology Cahiers, 2008)
From the commemoration of September 11 to the Holocaust memorial in Berlin, recent decades have witnessed a substantial increase in the number of new public memorials built in both Europe and the United States. This volume considers the contemporary explosion of public commemoration in terms of changed cultural and social practices of mourning, memory, and public feeling. Positing memorials as the physical and visual embodiment of our affective responses to loss, Erika Doss focuses especially on the memorial ephemera of flowers, candles, balloons, and cards placed at sites of tragic death in order to better comprehend how grief is mediated in contemporary commemorative cultures.